Left of Karl Marx : The Political Life of Black Communist Claudia Jones - Boyce Davies, Carole (Book collections on Project MUSE., 2007)
In Left of Karl Marx, Carole Boyce Davies assesses the activism, writing, and legacy of Claudia Jones (1915-1964), a pioneering Afro-Caribbean radical intellectual, dedicated communist, and feminist. Jones is buried in London's Highgate Cemetery, to the left of Karl Marx-a location that Boyce Davies finds fitting given how Jones expanded Marxism-Leninism to incorporate gender and race in her political critique and activism. Claudia Cumberbatch Jones was born in Trinidad. In 1924, she moved to New York, where she lived for the next thirty years. She was active in the Communist Pa.